Effectiveness of Sound‐Based Interventions for Improving Functional Outcomes in Children: A Systematic Review of the Evidence. - Vincent, Vanessa; Skaczkowski, Gemma; Hughes-Barton, Donna; Gunn, Kate M.; Hilton, Claudia (Occupational Therapy International, 2025)
Introduction: The aim of this review was to examine the evidence for sound‐based interventions in decreasing auditory hypersensitivity and improving behavioural and emotional regulation among children. Methods: A systematic review was conducted of primary research examining the use of sound‐based interventions to reduce auditory hypersensitivity and regulate emotion or behaviour. Studies were eligible if they were published in English in a peer‐reviewed journal, from January 2010 to March 2023. Studies of any design were included. Results: A total of 4741 titles were identified in the search. Eight papers were eligible, covering six different sound‐based interventions. Preliminary evidence highlights improvements in depression and anxiety symptomatology and improved behavioural outcomes including language, listening, and social behaviours. Heterogeneity was high across studies; they varied widely in sample size, population type, study design, and outcomes measured. Conclusions: There is preliminary evidence for the effectiveness of sound‐based interventions in improving auditory sensitivity and emotional and behavioural outcomes. However, there is a need for higher quality studies, including randomised controlled trials, and consistency in outcomes across studies to enable a clearer assessment of the evidence.